The golden rule - Cooper, Ilene; Swiatkowska, Gabi (New York : Abrams Books for Young Readers, 2007)
Grandpa explains that the golden rule is a simple statement on how to live that can be practiced by people of all ages and faiths, then helps his grandson figure out how to apply the rule to his own life.
Keywords: Golden rule -- Fiction; Conduct of life -- Fiction; Golden rule -- Juvenile fiction; Conduct of life -- Juvenile fiction; Conduct of life; Golden rule; Fiction; Juvenile works